Social work supports cyberbullied middle school students in the world and in Vietnam: Literature Review - Vu, Hong Nhung (Technium Social Sciences Journal, 2023)
Cyberbullying is considered a serious problem in recent decades in many nations, comprised of Vietnam. During the Covid – 19 pandemic, middle school students were one of cyberbullying victims whilst long – time learning online. Based on the literature analysis method, theory and reality research, purpose of recommending social work solutions so as to promote the efficiency of supporting cyberbullied middle school students, the author overviews domestic and foreign publications about social work supporting cyberbullied middle school students on 5 axes: The current circumstance of cyberbullying among students; The cultural and socio-economic impact on cyberbullying solves cyberbullying for middle school students; Policy and service system supports middle school students in countries; Support programs mitigate cyberbullying among students; The role of social work in supporting cyberbullied middle school students.